Міждисциплінарний підхід до оцінювання еколого-соціальної безпеки водних об'єктів – джерел господарсько-питного водопостачання - Дмитрієва, О.О.; Колдоба, І.В. (Екологічна безпека та природокористування, 2012)
In the article approach is offered for the estimation of water objects – sources of economic-drinkable water-supply, formed on theoretical bases of safety of man and environment. The complex of factors is presented, approaches and positions on the basis of which this estimation must produced in the conditions of increase of the anthropogenic loading.